PRINCIPLE OF OPENNESS: SOCIAL EFFECTS OF RECKLESS LEGAL CHANGES IN THE POLISH LEGAL SYSTEM (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2023)
Polish civil procedure has recently suffered from reckless legislative changes. At the same time, the protractedness of proceedings in Poland reach its peak: the simplest cases are being handled for years. The Polish legislature, looking for solutions, increasingly seeks to speed up proceedings at the expense of the guiding principles of civil procedure, including the principle of openness. This results in a demolition of many institutions of civil procedure that have taken years to shape. The paper presents an analysis of the changes that have taken place with regard to the principle of openness in civil proceedings, as well as the dilemmas that have arisen due to the restriction of openness. The considerations revolve around the subject of the guiding principles of the trial, in particular the principle of openness, the institutions that limit the principle of openness, and the conflict between the principle of openness and the demand for fast proceedings. The basic question is: how will ill-considered changes to the openness of proceedings affect citizens' perception of the judiciary? What will be social effects of reckless legal changes in order to speed up proceedings?
Keywords: Polish procedure, civil procedure, reckless legal changes, principle of openness, protractedness of proceedings.